Prognostic Significance of mTOR Expression in Recurrence Following Hepatic Metastasectomy in Colorectal Cancer - Fuat Aksoy; Secil Ak-Aksoy; Ahmet Karamustafaoglu; Cagla Tekin; Melis Ercelik; Berrin Tunca; Busra Oncel Duman; Ozgen Isik; Nesrin Ugras; Ekrem Kaya (Life)
Surgery is one of the most effective treatment methods for liver metastases developing from primary colorectal cancer (CRC). Despite the widespread application of surgical approaches, recurrence rates remain substantial. Although chemotherapy is frequently employed, the supporting evidence for its efficacy in this context remains inconclusive. In the present study, we aimed to identify potential predictors of post-metastasectomy recurrence by analyzing clinical, pathological, and molecular features of both primary colorectal tumors and their corresponding hepatic metastases. Specifically, we evaluated the expression of epithelial–mesenchymal transition (EMT) markers, cancer stem cell (CSC) markers, and selected oncogenic mRNAs (RAS, mTOR, and CMYC) in tissue samples from 84 patients. RAS and CMYC are well-known proto-oncogenes involved in cell proliferation and survival, while mTOR functions as a central regulator of cell growth and metabolism. Following liver metastasectomy, intra-hepatic recurrence was observed in 40.5% of the cases. Among the molecular markers analyzed, the EMT transcription factor SNAIL—which plays a critical role in cancer cell invasion and metastasis—and mTOR exhibited significantly elevated expression in metastatic lesions from patients who experienced recurrence. While SNAIL expression did not show a clear association with the time to recurrence, increased mTOR expression in metastatic liver tissue was significantly associated with both shorter recurrence-free survival and diminished overall survival (p < 0.001). Results showed that mTOR expression levels could be a clinically relevant predictive indicator of remnant liver recurrence. In patients with liver metastases, the use of mTOR inhibitors may be considered after hepatic metastasectomy.